KONTEKS PERTUNJUKAN LAGU-LAGU GAMELAN PAGUYUBAN BINA LARAS (TINJAUAN POLA PENYAJIAN) - Suranti Utami; Mahdi Bahar; Nursyirwan Nursyirwan (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT The form of the pattern presentation of gamelan songs in Bina Laras association is different in any of their performance. This can be seen in a wayang kulit performance and Sawahlunto people’s party events. While in festival, this association combines some Minangkabau traditional musical instruments into gamelan ensemble. This research used qualitative method supported by data from field and library research starting from doing survey and then collecting data by using the techniques of observation, interview and documentation. Presentation pattern of gamelan songs in Bina Laras association is different in each of their performance because Sawahlunto people are multiethnic people consisting of Javanese, Minangkabaunese, Bataknese, Sundanese and Tionghoa. In addition, half of these association members are teenagers who do not only come from the Javanese ethnic group but also come from other ethnic groups. So does the election of instruments and language used in every performance namely using the language of tansi. Keywords: pattern of presentation, youth, creativity, gamelan.